2018
DOI: 10.1097/md.0000000000011014
|View full text |Cite
|
Sign up to set email alerts
|

Primary Sjogren syndrome diagnosed simultaneously with localized amyloidosis of the lacrimal gland

Abstract: Introduction:Amyloidosis accompanied by Sjögren's syndrome (SS) has been reported to occur primarily in the skin, lungs, tongue, and mammary gland. However, SS in association with secondary amyloidosis is rarely reported, and knowledge of its relevance is inadequate. Here we report a case of primary SS diagnosed simultaneously with localized amyloidosis of the lacrimal gland.Case presentation:A 45-year-old woman complaining of a left eyelid mass was referred to the hospital and was diagnosed with localized amy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…In cases where amyloidosis accompanies SS, amyloidosis is diagnosed 1–25 years after the development of inflammation, during the course of SS, although in some cases these conditions have been diagnosed simultaneously. This may be the result of delayed diagnosis of SS in patients who previously had only mild or no symptoms associated with the disease [8] , which seems to be the case in our patient.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…In cases where amyloidosis accompanies SS, amyloidosis is diagnosed 1–25 years after the development of inflammation, during the course of SS, although in some cases these conditions have been diagnosed simultaneously. This may be the result of delayed diagnosis of SS in patients who previously had only mild or no symptoms associated with the disease [8] , which seems to be the case in our patient.…”
Section: Discussionmentioning
confidence: 71%
“…Amyloidosis in patients with primary SS is rare [1, 8] . The risk of developing AA amyloidosis is related to continuous, subclinical inflammation and, consequently to the magnitude and persistence of elevated AA amyloid levels [1] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When associated to PSS, amyloidosis is diagnosed 1 to 25 years after the diagnosis of the disease, although in some cases they were diagnosed simultaneously. This may be the consequence of a delayed diagnosis of PSS in patients who previously had only mild symptoms related to the disease [10], which seems to be the case among these patients. Despite being a common complication of chronic inflammatory disease, few studies have evaluated the natural history, prognostic markers and treatment of AA amyloidosis [11].…”
Section: Discussionmentioning
confidence: 93%
“…The patient described in this report was being treated for sarcoidosis uveitis. Since there have been reports of lacrimal amyloidosis complicated by systemic diseases such as Sjögren's syndrome, sarcoidosis, and multiple myeloma [9,10], the possibility of systemic amyloidosis was also considered. Several studies have reported that amyloidosis can be complicated by sarcoidosis [11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%